Gene flow and species cohesion following the spread of Schiedea globosa (Caryophyllaceae) across the Hawaiian Islands. - Dixon, C; Kapralov, M; Filatov, D (2011)
Island radiations are often regarded as natural laboratories that allow us to study evolution in action. The genus Schiedea (Caryophyllaceae) is one of the largest radiations of angiosperms in the Hawaiian Islands, and Schiedea globosa is one of the few species in the genus to be found on more than one of the main islands. DNA sequences from nineteen nuclear and three chloroplast regions show a pattern of colonization from older to younger islands (west to east), with a concomitant decrease in genetic diversity eastwards (π=0.53% for O'ahu, 0.43% for Moloka'i and 0.36% for Maui). While polymorphisms in the maternally inherited chloroplast have become fixed on different islands (F(ST)=0.804), significant gene flow between islands is inferred for the nuclear genome (F(ST)=0.270). This gene flow appears to be uneven, with most gene flow outwards from the central island. The extent of inter-island gene flow through wind pollination was assessed in an isolation-migration framework; the inferred rate, c. 1 migrant per generation, may be sufficient to prevent divergence of S. globosa populations and ensure cohesion of the species following the colonization of new islands.